The redundancy of the mammalian heterochromatic compartment. (April 2016) - Politz, Joan C Ritland; Scalzo, David; Groudine, Mark
Abstract : Two chromatin compartments are present in most mammalian cells; the first contains primarily euchromatic, early replicating chromatin and the second, primarily late-replicating heterochromatin, which is the subject of this review. Heterochromatin is concentrated in three intranuclear regions: the nuclear periphery, the perinucleolar space and in pericentromeric bodies. We review recent evidence demonstrating that the heterochromatic compartment is critically involved in global nuclear organization and the maintenance of genome stability, and discuss models regarding how this compartment is formed and maintained. We also evaluate our understanding of how heterochromatic sequences (herein named heterochromatic associated regions (HADs)) might be tethered within these regions and review experiments that reveal the stochastic nature of individual HAD positioning within the compartment. These investigations suggest a substantial level of functional redundancy within the heterochromatic compartment.